DESIGN OF KOST RENT INFORMATION SYSTEM - Lydia Salvina Helling; Hasanudin Hasanudin; Endang Wahyudi; A.A.Gede Ajusta (Kresnamedia Publisher, 2020)
Rumah Kost Hj. Gaby is one of the many boarding houses for rent around industrial areas and offices in the Tg. Priok area, North Jakarta. This boarding house still uses a board in front of the house to indicate that the house is rented out for boarding. This method is less effective in promoting the boarding house because prospective tenants must accidentally pass and see the promotion board. The down payment for boarding and monthly rent still has to meet directly with the owner of the boarding house so that it requires special time. The boarding rental information system that is designed is expected to help prospective tenants or tenants to make more practical order and payment transactions, in addition to helping boarding owners tidy up their boarding room rental management The methods used in this research are: interviews, observation, and literacy studies for data collection. Meanwhile, the model used for software development uses the Rapid Application Development Model (RAD). The results of this study are expected to assist boarding owners in promoting their boarding houses and also provide a more effective way of conducting transactions related to the boarding houses.